Timing of transcutaneous acupoint electrical stimulation for postoperative recovery in geriatric patients with gastrointestinal tumors: study protocol for a randomized controlled trial - Yin, Weijuan; Fang, Fang; Zhang, Yan; Xi, Lijuan (Frontiers in Medicine, 2025)
PurposeTo develop a study protocol for determining the optimal timing of Transcutaneous Electrical Acupoint Stimulation (TEAS) to enhance postoperative recovery in elderly patients. The study aims to evaluate different timing strategies for TEAS administration and their effects on postoperative outcomes, with the goal of improving clinical practices and guiding future research.MethodsA total of 266 geriatric patients who underwent radical resection of gastrointestinal tumors will be divided into seven groups: one control group (receiving standardized perioperative management), one sham intervention group (receiving TEAS treatment without electrical stimulation), and five intervention groups (receiving TEAS at different time intervals). The intervention groups will receive TEAS at bilateral Neiguan (PC6) and Zusanli (ST36) acupoints. The TEAS treatment will employ an altered frequency of 2/100 Hz with disperse-dense waveforms and an adjustable intensity, ensuring the stimulation remains below 10 mA and within a tolerable range for the patient. The device will output an asymmetrical biphasic pulse wave, with a pulse width of 0.2 ms ± 30%, based on electromagnetic compatibility basic performance testing. The primary outcome will assess changes in cognition, measured using neuropsychological tests administered preoperatively and 3 days postoperatively, as well as the Telephone Interview for Cognitive Status-Modified (TICS-m) at 1, 3, and 6 months postoperatively. Secondary outcomes will include preoperative and 3-day postoperative measurements of interleukin-6 (IL-6), S100 calcium-binding protein β (S100β), tumor necrosis factor alpha (TNF-α), insulin-like growth factor 1 (IGF-1), and C-reactive protein (CRP). Additional data will be collected on the time to postoperative exhaust, defecation, eating, and the first postoperative ambulation. Numeric Rating Scale (NRS) scores will be recorded before and on the third day after the operation, alongside Activities of Daily Living (ADL) and Braden scale scores, which will be assessed before the operation and at the time of discharge.DiscussionThis protocol aims to determine the optimal timing of TEAS for improving postoperative recovery in geriatric patients with gastrointestinal tumor.Clinical trial registrationClinicalTrials.gov, identifier NCT05482477.